Critical care nursing of the oncology patient - Routt, Meghan; Parks, Lisa, 1958- (Oncology Nursing Society, 2018)
Provides nurses with knowledge of how to optimally care for patients with cancer, including working collaboratively throughout the transition from the medical-surgical floor to the intensive care unit and back to the medical-surgical floor.